2014
DOI: 10.1016/j.jand.2014.04.017
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Food Refusal Related to Characteristics of Food in Children with Autism Spectrum Disorder and Typically Developing Children

Abstract: Parents of children with autism spectrum disorder (ASD) frequently report child food refusal based on characteristics of food. The present study sought to determine if parent report of food refusal based on the characteristics of food was: (1) greater in children with ASD than typically developing (TD) children; (2) associated with a greater percentage of foods refused of those offered; and (3) associated with fruit and vegetable intake. A modified food frequency questionnaire (FFQ) was used to determine overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
91
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(106 citation statements)
references
References 28 publications
5
91
0
10
Order By: Relevance
“…41,42 Several studies have documented nutrient inadequacy associated in children with ASD 14,17,43 as well as lower intakes of fruits and vegetables. 15,16,27 Mealtime stress represents an additional potential risk factor for the excess caloric intake associated with poor quality diets. 44 Qualitative studies document high levels of parent stress related to the restricted diet and feeding behaviors of children with ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 Several studies have documented nutrient inadequacy associated in children with ASD 14,17,43 as well as lower intakes of fruits and vegetables. 15,16,27 Mealtime stress represents an additional potential risk factor for the excess caloric intake associated with poor quality diets. 44 Qualitative studies document high levels of parent stress related to the restricted diet and feeding behaviors of children with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Children with ASD often exhibit selective eating, frequently resulting in low intakes of fruits and vegetables with ASD and high intakes of calorically dense foods. [14][15][16][17] As youth age, they are more likely to have access to more energy-dense snacks and less engagement in physical activity compared with the peers without ASD, 18 and their physical activity levels decline with age. 19,20 Parents of children with ASD report using television for its calming effect, 21 which may contribute to high levels of sedentary behavior.…”
mentioning
confidence: 99%
“…The texture of foods has consistently been identified as a related aspect of food acceptance. (Ahearn et al 2001; Hubbard et al 2014; Postorino et al 2015; Schreck & Williams 2006; Schreck et al 2004; Williams et al 2005). For example, using data from the current study, Hubbard et al (2014) found that texture and consistency of foods are highly correlated with parent report of food refusal in a sample of 53 children with ASD ages 3–11 years.…”
mentioning
confidence: 99%
“…Increasing evidence has shown that children with autism spectrum disorder (ASD) experience challenges in these daily routines and that their sensory differences often interfere with their ability to develop skills in these important daily routines Schaaf, Toth-Cohen, Johnson, Outten, & Benevides, 2011;Stein, Polido, & Cermak, 2012;Stein, Polido, Mailloux, Coleman, & Cermak, 2011). Eating difficulties are a frequent problem for children with autism (Hubbard, Anderson, Curtin, Must, & Bandini, 2014;Kral, Eriksen, Souders, & Pinto-Martin, 2013;Marí-Bauset, Zazpe, Mari-Sanchis, Llopis-González, & Morales-Suárez-Varela, 2014;Nadon, Feldman, Dunn, & Gisel, 2011a, 2011bSchreck & Williams, 2006;Schreck, Williams, & Smith, 2004;Suarez, Nelson, & Curtis, 2014) and may weaken their physical health Lukens & Linscheid, 2008;Sharp et al, 2013), cause difficulty during family mealtimes and milieu (Bagby, Dickie, & Baranek, 2012;Schaaf et al, 2011;Suarez, Atchison, & Lagerwey, 2014), and impede participation in the educational setting (Koenig & Rudney, 2010).…”
mentioning
confidence: 99%